Adab dalam Menuntut Ilmu Menurut Perspektif Syeikh Muhammad Syakir dalam Kitab Washoya Al Abaa’ Lil Abnaa - Eva Defani Suti; Eko Surbianto; Khambali (Bandung Conference Series: Islamic Education, 2022)
Abstract. The Indonesian nation is currently reaching its peak in facing various educational problems, especially the decline of morals and the loss of adab. Adab can be interpreted as a reflection of a person's good or bad. The word adab is usually addressed specifically to pupils. Students are defined as people who want to gain knowledge. Science is a knowledge that can provide instructions for a person to understand between right and wrong, as well as the provision of man to obtain salvation and well-being both in the world and in the hereafter. Based on this phenomenon, the problem in this study is formulated as follows: "Who is Sheikh Muhammad Syakir?" And "How is the adab of students in studying according to the perspective of Sheikh Muhammad Syakir in the Book of Washoya Al-Abaa' lil Abnaa?". This type of research is Library Research (literature research). The data collection technique used in this study is a document related to the studying adab to Sheikh Muhammad Syakir. Meanwhile, the data analysis technique uses a content analysis method related to primary data and secondary data. The results of the study were: 1) Sheikh Muhammad Syakir was a great scholar whose one of his works was the book of Washoya Al-Abaa' lil Abnaa. 2) Adab studied in the book of Washoya Al-Aba‟ Lil Abna by Sheikh Muhammad Syakir is a commendable part of morals that must be possessed by students in studying so that it is facilitated, launched, and useful for the knowledge they have gained. Abstrak. Bangsa Indonesia saat ini mencapai puncak dalam menghadapi berbagai permasalahan pendidikan, khususnya kemerosotan akhlak dan hilangnya adab. Adab dapat dimaknai sebagai cerminan dari baik buruknya seseorang, terhormat atau tercelanya nilai seseorang, mulia atau hinanya seseorang. Kata adab biasanya ditujukan khusus kepada murid. Murid diartikan sebagai orang yang menghendaki untuk mendapatkan ilmu pengetahuan. Ilmu adalah sebuah pengetahuan yang bisa memberikan petunjuk bagi seseorang untuk memahami antara yang benar dan yang salah. Berdasarkan fenomena tersebut, maka permasalahan dalam penelitian ini dirumuskan sebagai berikut: “Siapakah Syeikh Muhammad Syakir itu?” Dan “Bagaimana adab murid dalam menuntut ilmu menurut perspektif Syeikh Muhammad Syakir dalam Kitab Washoya Al-Abaa’ lil Abnaa?”. Jenis penelitian ini merupakan penelitian Library Research (penelitian kepustakaan). Teknik pengumpulan data yang dipakai dalam penelitian ini adalah dokumen yang berkenaan dengan adab menuntut ilmu menurut Syeikh Muhammad Syakir. Sedangkan teknik analisis datanya menggunakan metode analisis isi (content analysis) yang berkaitan dengan data primer dan data sekunder. Hasil dari penelitian in: 1) Syeikh Muhammad Syakir adalah seorang ulama besar yang salah satu karyanya itu adalah kitab Washoya Al-Abaa’ lil Abnaa. 2) Adab menuntut ilmu dalam kitab Washoya Al-Aba‟ Lil Abna karya Syeikh Muhammad Syakir adalah bagian akhlak terpuji yang harus dimiliki oleh peserta didik dalam menuntut ilmu supaya dimudahkan, dilancarkan, serta bermanfaat ilmu yang diperolehnya.